O024 Weight loss surgery in obese patients with obstructive sleep apnoea is associated with increased inter-hemispheric electroencephalographic coherence. (7th October 2021) - Duce, B; Ryan, A; Hukins, C
Abstract: Introduction: Electroencephalogram (EEG) analysis of obstructive sleep apnoea (OSA) patients has shown reductions in both delta band frequency power and interhemispheric coherence. Weight loss surgery is increasing in popularity and is often effective in reducing the symptoms and severity of OSA. No study has examined the effects of weight loss surgery on the sleep EEG of OSA patients. Methods: Twenty patients underwent diagnostic polysomnography (PSG) prior to- and twelve months after weight loss surgery. Quantitative EEG analysis was conducted to calculate spectral power (fast fourier transform with four second overlapping windows) as well as amplitude and phase coherence between the two hemispheres (C3/C4 electrodes). Results: Weight loss surgery was successful in reducing weight (137±17 kg vs 102±17kg P<0.001 for pre- and post-surgery, respectively), and OSA severity (Apnoea-Hypopnoea Index: 26±15 events/hour vs 10±12 events/hour P<0.001 for pre- and post-surgery, respectively). Stage N1 proportions were slightly decreased (12±7% vs 9±8%; P=0.039 for pre- and post-surgery, respectively) but all other stages were unchanged. Increases in interhemispheric phase coherence was observed following weight loss surgery, with significant changes observed in theta (-0.07±0.09 degrees vs -0.03±0.03 degrees P=0.035), alpha (-0.12±0.13 degrees vs -0.03±0.06 degrees P=0.008), sigma (-0.19±0.18 degrees vs -0.07±0.07 degrees P=0.011) and beta (-0.29±0.25 degrees vs -0.11±0.09 degrees P=0.004) band frequencies. There were no differences in EEG spectral power or interhemispheric amplitude coherence. Discussion: Sleep EEG coherence, a putative marker of neurocognitive susceptibility in OSA, improves following weight loss surgery. Further studies are needed to determine the functional consequences of these EEG changes.